2012
DOI: 10.1371/journal.pone.0043903
|View full text |Cite
|
Sign up to set email alerts
|

Glycoform and Net Charge Heterogeneity in gp120 Immunogens Used in HIV Vaccine Trials

Abstract: BackgroundThe RV144 clinical trial showed for the first time that vaccination could provide modest but significant protection from HIV-1 infection. To understand the protective response, and to improve upon the vaccine's efficacy, it is important to define the structure of the immunogens used in the prime/boost regimen. Here we examined the heterogeneity in net charge, attributable to glycoform variation, of the gp120 immunogens contained in the AIDSVAX B/E vaccine.Methodology/Principal FindingsIsoelectric foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 51 publications
7
52
0
Order By: Relevance
“…Transfections were carried out with polyethyleneimine, and the supernatant was collected on day 3 or day 4 (55). For gD-tagged constructs, immunoaffinity chromatography was used to purify the proteins as described previously (47). To purify His 6 -tagged constructs, HisTrap HP columns (GE Healthcare) were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transfections were carried out with polyethyleneimine, and the supernatant was collected on day 3 or day 4 (55). For gD-tagged constructs, immunoaffinity chromatography was used to purify the proteins as described previously (47). To purify His 6 -tagged constructs, HisTrap HP columns (GE Healthcare) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were digested as described previously (47). Samples were run on NuPAGE (Invitrogen) precast gels (4 -12% BisTris) with MES running buffer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negatively charged surfaces have been characterized in the early crystal structures of HIV-1 gp120 in complex with CD4 (26), and more recently changes in the net negative charge of the fourth variable (V4) domain of gp120 were shown to influence HIV-1 coreceptor usage (7). Furthermore, analysis of gp120 proteins contained in the AIDSVAX B/E vaccine indicated that the producer cell can influence the net surface negative charge of gp120, and consequently the antigenicity of the proteins, which could in turn influence susceptibility to neutralization (27). Preliminary data from our laboratory indeed demonstrated a dramatic reduction of XCL1 activity against HIV-1 pseudoviruses produced in continuous cell lines, compared to virus produced in primary cells which displays a more physiological glycosylation pattern (C. Guzzo et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…39 Both the VAX003 study and the RV144 study used the same vaccine design platform: bivalent AIDSVAX B/E vaccine prepared from gp120s from the MN and A244 strains of HIV-1. Both proteins were made in CHO cells and purified by immunoaffinity chromatography (no selection for a particular type of carbohydrate).…”
Section: Hiv-1 Immunogen Designmentioning
confidence: 99%